Treating beyond symptoms with a view to improving patient outcomes in inflammatory bowel diseases. (1st September 2014) - Sandborn, William J.; Hanauer, Stephen; Van Assche, Gert; Panés, Julián; Wilson, Stephanie; Petersson, Joel; Panaccione, Remo
Abstract: Background and aims: Treatment goals in inflammatory bowel diseases are evolving beyond the control of symptoms towards the tight control of objectively-measured gastrointestinal inflammation. This review discusses the progress and challenges in adopting a treat-to-target approach in inflammatory bowel diseases. Methods: Evidence from the literature that highlights current thinking in terms of treating-to-target in patients with inflammatory bowel diseases is discussed. Results: Monitoring for objective evidence of inflammation using endoscopy, cross-sectional imaging or laboratory biomarkers may be a useful approach in inflammatory bowel diseases; however, setting the appropriate treatment goal remains a challenge. Deep remission (a composite of symptom control and mucosal healing) may now be a realistic target in Crohn's disease; however, it remains to be proven that achieving deep remission will modify the long-term disease course. Assessing prognosis at an early stage of the disease course is essential for the development of an appropriate management plan, with the rationale of adapting treatment to disease severity. An algorithm has been proposed for the treatment of early Crohn's disease that involves early treatment with immunosuppressants and tumour necrosis factor antagonists, in the hope of preventing structural bowel damage. Conclusions: Treating beyond symptoms will require a clear management plan influenced by disease severity at presentation, clinical and biological prognostic factors, achievement and maintenance of clinical and biological remission and pharmacoeconomics.